Odpowiedzi

2009-10-29T20:04:43+01:00
A-2(b-1)+2[-5(a+1)-0,5a]+2b przy a=4/5 b=1/4

0,8-2(0,25-1)+2[-5(0,8+1)-0,5X0,8] + 2X 0,25

0,8-0,5+2+2 [-4-5-4] + 0,5

2,3+ 26 + o,5 = 28,8


sorka;] ale to juz powinno byc okej;]
2009-10-29T20:06:06+01:00
Człowieku przecież to banalne

a-2(b-1)+2[-5(a+1)-0,5a]+2b przy a=4/5 b=1/4:

4/5-2(1/4-1)+2[-5(4/5+1)-0,5*4/5]+2*1/4

4/5-2(-3/4)+2[-5(9/5)-2/5]+2/4

4/5+6/4+2[-45/5-2/5]+2/4

16/20+30/20+2[-47/5]+2/4

46/20-94/5+2/4

46/20-376/20+10/20

-320/20 = -16
Najlepsza Odpowiedź!
2009-10-29T20:12:22+01:00
A-2(b-1)+2[-5(a+1)-0,5a]+2b
a=4/5 b=1/4

4/5-2(1/4-1)+2[-5(4/5+1)-0,5*4/5]+2*1/4=

=4/5-2*(-3/4)+2[-5*(9/5)-4/10]+2/4=

=4/5-(-6/4)+2[-45/5-4/10]+2/4=

=16/20+30/20+2[-9-8/20]+10/20=

=46/20+2[-188/20]+10/20=

=56/20-376/20=

=-320/20=

=-16